Effect of Ferrous Sulphate on Prevalence of Anemia Among Students of Technical and Medical Institute, Al-Mansoor, Baghdad - Al-Kaisey, H. T.; muhammed, S. A.; Saaed, A. H.; Al-Sadi, F. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted to investigate the prevalence of anemia among students (males and females) of the Technical and Medical Institute/ Al-Mansoor, Baghdad. 135 students aged 20 -22 years were subjected. Twenty-one students were found to be anemic. The prevalence of anemia among students was 15.55%, with no significant difference to sex. Then, the anemic students were treated with tablets of ferrous sulfate twice daily for 60 days. The treatment markedly elevated the hemoglobin concentration of both males and females and decreased the prevalence of anemia from 15.55% to 5.92%. The decrease in prevalence of anemia tended to be higher in anemic females as than anemic males (15.51% and 15.58% before treatment and 3.44% and 7.79% after treatment, respectively). So, treatment with ferrous sulfate tablets can effectively, reduce the prevalence of anemia among students and may reduce the complications of anemia among students.